2021
DOI: 10.3389/fonc.2021.639059
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Immune Infiltration and Construction of a Prediction Model for Overall Survival in Melanoma Patients

Abstract: Reports indicate that the use of anti-programmed cell death-1 (PD-1) and death ligand-1 (PD-L1) monoclonal antibodies for the treatment of patients diagnosed with melanoma has demonstrated promising efficacy. Nonetheless, this therapy is limited by the resistance induced by the tumor microenvironment (TME). As such, understanding the complexity of the TME is vital in enhancing the efficiency of immunotherapy. This study used four different methods to estimate the infiltrating level of immune cells. Besides, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 65 publications
1
11
0
Order By: Relevance
“…In this study, the UV-low cluster showed a significantly lower leukocyte fraction, proportion of tumor-infiltrating leukocytes, CYT score, and TCR richness than the UV-high cluster. It has been established that low immune cell infiltration is associated with poor clinical outcome ( Barnes and Amir, 2017 ; Thorsson et al, 2018 ; Li et al, 2021 ). Therefore, the poorer survival in the UV-low cluster may be explained by lower activation of antitumor immunity.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the UV-low cluster showed a significantly lower leukocyte fraction, proportion of tumor-infiltrating leukocytes, CYT score, and TCR richness than the UV-high cluster. It has been established that low immune cell infiltration is associated with poor clinical outcome ( Barnes and Amir, 2017 ; Thorsson et al, 2018 ; Li et al, 2021 ). Therefore, the poorer survival in the UV-low cluster may be explained by lower activation of antitumor immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Due to inter-cell crosstalk, different immune cells are often closely regulated and hence co-infiltrate the tumor microenvironment 29 . To demonstrate this, we applied eight transcriptome-based cell-type quantification methods [15][16][17][18][19][20][21][22][23][24][25] to metastatic melanoma, which is known to be a highly immune infiltrated cancer type (immune "hot") 30,31 . As expected, estimated cell abundances were strongly positively correlated to each other (Figure S1A).…”
Section: Gene Pair Analysis Disentangles Expression Correlations Caus...mentioning
confidence: 99%
“…Melanoma is divided into cutaneous and noncutaneous tumors based on the location of the primary tumor [4]. Cutaneous melanoma, an invasive cancer with high metastatic potential, occurs from cells in the skin and mucous membranes called melanocytes, which are responsible for pigmentation in the skin [3,5,6]; however, it accounts for a small percentage (<5%) of all cancers [7]. Although the 5-year survival rate for melanoma patients is below 5, the chance of survival is less than 1% when metastasis occurs [7].…”
Section: Introductionmentioning
confidence: 99%